Time to rethink sovereignty (2014)
Examines the October 4, 2013, ruling of the Caribbean Court of Justice in the case brought by Jamaican traveller Shanique Myrie against the Barbados Government which denied her entry to the island on March 14, 2011.
Keywords: SOVEREIGNTY